Urban Roads Resealing Project (URRP) under Ministry of Works and Transport: Are the outputs and outcomes being achieved? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
The Urban Roads Resealing Project (URRP) was instituted in June 2011 will end in June 2020. It aimed at rehabilitating or upgrading some of the major roads and streets within urban centres by force account. The Force Account Policy was introduced in 2012 and entails having internal skilled personnel, equipment and funds for road activities. To this effect, the Government of Uganda (GoU) acquired a loan from the Republic of China amounting to USD 100 million which was used to purchase 1,425 pieces of new road equipment. The project cost was estimated at Ug shs 147.9 billion which was revised to Ug shs134.42 billion and was to be financed by the GoU. Given the project life-span of nine (9) financial years (FYs), the annual releases in the range of Ug shs 11.50 -17.5 billion had to be released to the project for it to achieve its intended output and consequently, contribute to improved transportation system as an outcome. The Ministry of Works and Transport (MoWT) as the implementer plans to rehabilitate or upgrade to bitumen standard, roads in at least three (3) urban councils in every FY. Other works undertaken arise from directives and pledges to construct tarmac for government institutions and agencies. The project also fulfills some of the President’s directives relating to road works that are outside the UNRA’s mandate and beyond the scope of Local Governments (LGs). This Briefing Paper elucidates the level of achievement of the URRP key planned outputs by 31st December 2018; and assesses whether the project is likely to achieve its planned outputs and the expected National Development Plan (NDP) II outcomes by June 2020. It further highlights key obstacles faced during implementation, lessons learnt and possible recommendations. Performance Rating: A quantitative scoring method was used to rate the extent to which the planned outputs were achieved. The performance scores are as follows: Very Good (90% and above); Good (70%-89%); Fair (50%-69%) and Poor (Less than 50%).